The effectiveness of core stability exercises on pain in patients with low back pain: a meta-analysis - W. Wahyuni; Noofi Emma Kurnia (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Introduction: Lower back pain (LBP) results from stress in the muscles in the lower back. The pain patients with typical back pain feel is between the lower corner of the costa and the lumbosacral caused by muscle tension in the lower back area. Based on the Results of Basic Health Research (2018), people with low back pain cannot be ascertained in Indonesia, but it is estimated to be between 7.6% to 37%. One intervention that can be given to reduce pain in patients with LBP is core stability exercise. Meta-analysis studies using PICO. P: patients with non-specific LBP. I: core stability exercise. C: non-core stability exercise. O: decrease in pain. Methods: The method of this study was a systematic review where data collection of the results of this research is carried out through searches on the PubMed and Scopus websites. Keywords used include: